2018
DOI: 10.1016/j.canep.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Testicular cancer among US men aged 50 years and older

Abstract: Given the distinct time-trends and age-specific patterns of testicular cancer in men aged ≥50 years, additional investigation of risk factors for these tumors is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Even though the median age at diagnosis of spermatocytic tumor is age 50 years, the incidence is always lower than that of seminoma. Although previous studies have found modest, nonsignificant, increases (61) and decreases (4) in the rates of spermatocytic tumor, the finding a statistically significant decrease in incidence is novel.…”
Section: Discussionmentioning
confidence: 77%
“…Even though the median age at diagnosis of spermatocytic tumor is age 50 years, the incidence is always lower than that of seminoma. Although previous studies have found modest, nonsignificant, increases (61) and decreases (4) in the rates of spermatocytic tumor, the finding a statistically significant decrease in incidence is novel.…”
Section: Discussionmentioning
confidence: 77%
“…PT-DLBCL accounts for 80-98% of all primary testicular lymphomas and~1% of all non-Hodgkin lymphoma cases. 104,105 PT-DLBCL is the most common testicular cancer among men >50-60 years of age. The median age is 65 years (range 10-96 years).…”
Section: Epidemiologymentioning
confidence: 99%
“…Tumors originating from testicular adnexa, including rete testis, or tunica vaginalis (mesothelial cells) and some embryonic structures that normally involute during fetal life, such a műllerian ducts, are also quite rare (16)(17)(18)(19)(20). Metastatic tumors to the testis and lymphoma are rare but must be considered in the differential diagnosis, especially in elderly patients (21,22).…”
Section: Clinical Sciencementioning
confidence: 99%